The Implementation of Collaborative Governance in Addressing Child Sexual Violence in Pekanbaru City, Indonesia - Mustiqowati Ummul Fithriyyah; Alvitriah Nurkholiva (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2026)
This study aims to analyze the implementation of Collaborative Governance in addressing cases of child sexual violence in Pekanbaru City by employing three main indicators: collaborative dynamics and resources, collaborative actions, and impacts and adaptation. The research adopts a descriptive qualitative approach through in-depth interviews, observation, and documentation involving stakeholders engaged in victim handling, including women and child protection service agencies, relevant local government offices, law enforcement authorities, healthcare providers, non-governmental organizations, and the community. The findings reveal that cross-sector collaboration has been established through coordination mechanisms; however, it has not been consistently implemented due to limited human resources, a shortage of professional counselors and assistants, and constrained budget support. Collaborative actions such as psychological assessments, legal assistance, and service referrals have been carried out, yet remain suboptimal because of procedural differences among institutions and the absence of integrated standard operating procedures (SOPs). This collaboration has contributed to improved service access and accelerated case handling, although stronger coordination and continuous evaluation are still required. The study reinforces the finding that the effectiveness of collaborative governance in child protection is highly dependent on the harmonization of inter-agency SOPs as well as the strengthening of institutional capacity and supporting resources.